Những thông tin cơ bản về cá và nghề cá trên sông Mê kông - Geheb, Kim; Pukinskis, Ilse (CGIAR Challenge Program on Water and Food, 2012)
Reviews Mekong fishery basics and current literature on the impact of dams on fish migrations and habitats, biodiversity, aquaculture production and reservoir fisheries.